The features of genres in new media - Shindaliyeva М.Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article analyzes genre features in new media in Kazakhstan, the transformation of genres, the advantages and features of internet journalism. The differences and similarities between new media and traditional media are considered and a comprehensive analysis of organizational and technological changes in Information, Broadcasting activities is carried out. The specifics of the functioning of internet journalism in accordance with the requirements of society, the preparation of journalistic materials by journalists are studied in detail. The specifics of the new mass media of an advanced type, in which various internet sites and social institutions are diversified both in the way of presenting information, competing with traditional media, and the presence of own sites of traditional mass media, the expansion of the audience in the course of convergence of the content of modern media, and the increase in platforms for transmitting and posting information are analyzed by specific examples. The reason why the modern genre system of internet publications has not yet been fundamentally studied, the reasons for the increase in the number of online publications and the change in genres are revealed.